PENGARUH HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MELALUI MARKETPLACE SHOPEE DENGAN RATING PENJUALAN TOKO SEBAGAI VARIABEL MODERASI - Nuri Ma'rifatul Laily; Vivin Maharani Ekowati (JURNAL LENTERA BISNIS, 2023)
This research was conducted with the aim of knowing the effect of price and brand image on purchasing decisions at Shopee with store sales ratings as a moderating variable. This study uses purposive sampling with the criteria of using a shopee which has made a purchase with at least 2 transactions with 102 respondents. This type of research is quantitative research by collecting data by distributing questionnaires through Google Form. Data were analyzed using a simple regression analysis test and moderating regression analysis using the SPSS 16 program. The results indicate that purchase decision at Shopee is influenced by the price and brand image. Store sales ratings weaken the relationship between price, brand image, Shopee purchase decisions.Key words: Price, Brand Image, Store Sales Rating, Buying Decision